A Study to Compare the Analgesic Efficacy of Intrathecal Bupivacaine Alone with Intrathecal Bupivacaine Midazolam Combination in Patients Undergoing Elective Infraumbilical Surgery. (14th May 2013) - Chattopadhyay, Anirban; Maitra, Souvik; Sen, Suvadeep; Bhattacharjee, Sulagna; Layek, Amitava; Pal, Sugata; Ghosh, Kakali
Abstract : Spinal anaesthesia, which is one of the techniques for infraumbilical surgeries, is most commonly criticized for limited duration of postoperative analgesia. Several adjuvants have been tried along with local anesthetic for prolonging the duration of analgesia. In this study, we have observed the effect of midazolam as an adjuvant in patients undergoing infraumbilical surgery. In this prospective, randomized, double blinded, and parallel group and open label study of 90 adult patients aged 18–60 years, of American Society of Anaesthesiologists (ASA) status I and II, scheduled for elective infraumbilical surgery, were randomly allocated in two groups. Each patient in group "B" received hyperbaric bupivacaine 12.5 mg along with 0.4 mL of normal saline in the subarachnoid block, and patients of group "BM" received 12.5 mg hyperbaric bupivacaine along with preservative free midazolam 0.4 mL (2 mg). We found that use of midazolam as adjuvant with the local anesthetic in spinal anaesthesia significantly increases the duration of analgesia (median 320 min versus 220 min) and motor block (median 255 min versus 195 min) but decreases the incidence of postoperative nausea-vomiting (PONV).